Falling through the cracks: Increased vulnerability and limited social assistance for TB patients and their households during COVID-19 in Cape Town, South Africa. - Lieve Vanleeuw; Wanga Zembe-Mkabile; Salla Atkins (Public Library of Science (PLoS), 2022)
Amid the COVID-19 crisis, Tuberculosis (TB) patients in South Africa, as elsewhere, faced increased vulnerability due to the consequences of the COVID-19 response such as loss of income, challenges to access diagnostic testing, healthcare services and TB medication. To mitigate the socio-economic impact of the pandemic, especially among the most vulnerable, the South African government expanded social assistance programmes by creating the Social Relief of Distress grant (SRDG), the first grant for unemployed adults in South Africa. Our study investigated how TB patients experienced the COVID-19 pandemic and the ensuing socio-economic fallout, how this affected their health and that of their household, income and coping mechanisms, and access to social assistance. We interviewed 15 TB patients at a health facility in Cape Town and analysed data thematically. To situate our findings, we adapted the United Nations' conceptual framework on determinants of vulnerability and resilience during or following a shock such as climate shocks or pandemics. We found increased vulnerability among TB patients due to a high exposure and sensitivity to the COVID-19 shock but diminished coping capacity. The loss of income in many households resulted not only in increased food insecurity but also a decreased ability to support others. For the most vulnerable, the loss of social support meant resorting to begging and going hungry, severely affecting their ability to continue treatment. In addition, most participants in the study and especially the most vulnerable, fell through the cracks of the most extensive social assistance programme in Africa as few participants were accessing the special COVID-19 SRDG. Targeted social protection for TB patients with a heightened vulnerability and low coping capacity is urgently needed. TB patients with a heightened vulnerability and low coping capacity should be prioritized for urgent assistance.